FAKTOR-FAKTOR YANG MEMPENGARUHI IMPLEMENTASI ACTIVITY BASED COSTING - Bulkia, Sri (JEA17: Jurnal Ekonomi Akuntansi, 2021)
This article shows that factors such as leadership support, external environment, cost-saving mechanisms, user attitudes, and company size are likely to have an influence on the implementation of Activity Based Costing. The research objective is to examine the relationship of these factors in the implementation of Activity Based Costing among Small and Medium Units in South Kalimantan so that they can contribute to further studies regarding activity-based costs in management accounting. The type of research used is quantitative research with a survey approach. Sampling using stratified random sampling and and obtained a sample of 35 respondents. The type of data used in this research is primary data obtained from questionnaires distributed to entrepreneurs and interviews, while secondary data is obtained from literature and the internet. The data analysis technique used in this study is multiple regression analysis. The results show that all variables have an influence on the implementation of Activity Based Costing.